Model Komunikasi Humas Pemerintah Daerah dalam Penerapan Keterbukaan Informasi Publik (Studi Deskriptif pada DPRD Kota Padang dan DPRD Kabupaten 50 Kota) - Havifi, Ilham; Marta, Revi; Diego; Sari, Lusi Puspika; Lani, Oktri Permata (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
Communication plays a pivotal role in the endeavor to achieve success, which, in this study, is examined through the lens of government public relations' communication in the political context, to channel the aspirations of the community through political communication in the Regional People's Representative Council (DPRD) of West Sumatra. The government PR of the DPRD plays a significant role in conveying information to the public regarding the performance of the DPRD as the vehicle for public aspirations in the political arena and the democratic processes in Indonesia, through the study of political communication. This research delves into the processes, characteristics, power relations from the perspective of political communication, specifically within government PR. The research analysis commences by mapping the issues faced by Government PR as Information and Documentation Management Officials, who function as the custodians and conveyors of documents held by Public Bodies in accordance with the mandate of Law No. 14/2008 on Public Information Disclosure in the DPRD of Cities and Regencies in West Sumatra. The research methodology employs a qualitative approach with a Constructivist Paradigm. The research subjects encompass government PR officials in the DPRD of West Sumatra, members of the DPRD, media practitioners, political activists, and other relevant stakeholders. The research findings observe a model of political communication by local government PR officers, implemented by the Information and Documentation Management Officials (PPID) of the DPRD in the City of Padang and the 50 Districts in the West Sumatra Province, in order to enhance public trust through effective public information disclosure.